Família, escola e educação matemática: um estudo em localidade de colonização alemã do Vale do Rio dos Sinos – RS - Junges, Débora De Lima Velho (Universidade do Vale do Rio dos Sinos, 2012)
The Master Dissertation aims at discussing the family-school relationship with regards to mathematics education, more specifically, this relationship in the EMEF Tiradentes, peasant multigrade school located in Novo Hamburgo, municipality of German colonization of the region of Vale do Rio dos Sinos - RS. In a specific way, it examines how the form of life of German colonization of Rio Grande do Sul started in the nineteenth century is intertwined with the form of life of that school; analyzes how, from the pedagogical point of view, that multigrade class of was organized; discusses how the participants described the family relationships with school through the practice of homework, and, about mathematics education in relation to school mathematics homework, identifies as are described by the participants of the language games and practiced by the families and that practiced in the form of school life. The theoretical tools of the study are linked to the field of Ethnomathematics in their intersections with the theories of Michel Foucault and Wittgenstein's ideas which were presented in his book Philosophical Investigations. The research material consists of interviews with seven families linked to EMEF Tiradentes, interview with the teacher of the multigrade class, classroom observation and parents meeting and analysis of documents EMEF Tiradentes. The main research findings indicate that: regarding the practices of EMEF Tiradentes there is no evidence that can relate the life form of German colonization of Rio Grande do Sul with the way of life of EMEF Tiradentes. The grammar of the school mathematics practiced in the class of multisseriate EMEF Tiradentes was consisted of a set of language games marked by writing and present formalism in the use of algorithms; the families described the aid to homework as a major form of family involvement in the educational issues, and was possible to identify family resemblances that approached the mathematical language games practiced by way of school life and the language games practiced by the families when these helped their children with their math homeworks.
Keywords: Relação família-escola; Educação matemática; Etnomatemática; Dever de casa; Family-school relationship; Mathematics education; Ethnomathematics; Homework; ACCNPQ::Ciências Humanas::Educação